Differences in Prosocial Behavior of 5 - 6 Year Old Children in Coastal and Non-Coastal Areas of North Bengkulu Regency - Pundawa Sari, Noti; Suryadi, Didik; Indrawati (CV Media Inti Teknologi, 2024)
This study aims to describe the differences in prosocial behavior of children aged 5-6 years in coastal and non-coastal areas of North Bengkulu Regency. By using a comparative quantitative research approach. The study population was 6 coastal sub-districts and 13 non-coastal areas in North Bengkulu and the sample used multistage sampling which had several stages, the first stage used cluster sampling techniques to select coastal sub-districts and non-coastal sub-districts in North Bengkulu Regency, the second stage used simple random sampling techniques used to select coastal and non-coastal villages, obtained a sample of 45 children. The data collection technique used a questionnaire. The research data analysis was Independent Sample T test. The results showed prosocial behavior from 5 sub-indicators (helping, cooperating, sharing feelings, acting honestly, and giving charity) in coastal areas with an average of 2.372 on low criteria, while non-coastal areas with an average of 2.41 on low criteria. There is no significant difference between the prosocial behavior of children aged 5-6 years in coastal and non-coastal areas of North Bengkulu Regency.